EXPLORING THE ROLE OF WORK-LIFE BALANCE AND JOB SATISFACTION IN SHAPING ORGANIZATIONAL CITIZENSHIP BEHAVIOR AT PT. BALI FOAM NUSA MEGAH DENPASAR - Rahayu, Kadek Linda Putri; Prastyadewi, Made Ika; Adhika, I Nyoman Resa (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2025)
Organizational citizenship behavior (OCB) is essentially a two-way process used by many companies to encourage and influence their employees' overall engagement with the company and their tendency to behave beyond their job responsibilities. This study aims to determine the effect of work-life balance and job satisfaction on organizational citizenship behavior at PT. Bali Foam Nusa Megah Denpasar. This research was conducted at PT. Bali Foam Nusa Megah Denpasar with a total sample of 52 employees. The sampling technique used in this study was saturated sampling. Data collection was carried out through observation, interviews, questionnaires, and documentation studies. The data analysis technique used in this study was multiple linear regression analysis processed using SPSS version 26 software. Based on the analysis results, this study shows that work-life balance has a positive and significant effect on organizational citizenship behavior at PT. Bali Foam Nusa Megah Denpasar. This means that the better the work-life balance, the better the organizational citizenship behavior at PT. Bali Foam Nusa Megah Denpasar. Work-life balance has a positive and significant effect on job satisfaction at PT. Bali Foam Nusa Megah Denpasar. This means that the better the work-life balance, the better the job satisfaction at PT. Bali Foam Nusa Megah Denpasar. Job satisfaction has a positive and significant effect on organizational citizenship behavior at PT. Bali Foam Nusa Megah Denpasar. This means that the better the job satisfaction, the better the organizational citizenship behavior at PT. Bali Foam Nusa Megah Denpasar.